Interactive Unawareness - Aviad Heifetz; Martin Meier; Burkhard C. Schipper (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
The standard state-spaces of asymmetric information preclude non-trivial forms of unawareness (Modica and Rustichini, 1994, Dekel, Lipman and Rustichini, 1998). We introduce a generalized state-space model that allows for non-trivial unawareness among several individuals, and which satisfies strong properties of knowledge as well as all the desiderata on unawareness proposed this far in the literature.
urn:nbn:de:bvb:19-epub-13498-0
Keywords: C70; C72; D80; D82; 330; unawareness; awareness; knowledge; interactive epistemology; speculative trade; bounded perception